Economically imperative Ananas comosus diseases, status, and its control measures documented in producing countries - Mohd Anuar, Intan Sakinah; Nusaibah, Syd Ali; Sapak, Zaiton (Universiti Putra Malaysia Press, 2024)
Ananas comosus, commonly known as pineapple, is a fruit with large potential market as a commodity and commercial fruit. Numerous pests and diseases affect pineapple, directly or indirectly by lowering the quality and quantity. The fungal causative agents, namely Fusarium ananatum and Thalaromyces stolii (previously named as Penicillium funiculosum) causes fruitlet core rot (FCR) and fusariosis by Fusarium guttiforme. Bacteria heart rot (BHR) is an infection by Erwinia chrysanthemi or newly known as Dickeya zeae. Nevertheless, mealybug wilt of pineapple (MWP) is another pineapple treat to susceptible pineapple varieties caused by pineapple mealybug wilt associated viruses (PMWaVs). Other diseases include destruction caused by pathogenic nematodes. This review discusses the status of these diseases and the control measures, which greatly affect the economy of pineapple-producing countries due to the economic significance of these crops. Growers need up-to-date information on the identity of the diseases that affect pineapple crops in the various countries that produce them in order to effectively manage the diseases in the field.